The Multiple Localized Glyceraldehyde-3-Phosphate Dehydrogenase Contributes to the Attenuation of the Francisella tularensis dsbA Deletion Mutant - Pavkova, Ivona; Kopeckova, Monika; Klimentova, Jana; Schmidt, Monika; Sheshko, Valeria; Sobol, Margarita; Zakova, Jitka; Hozak, Pavel; Stulik, Jiri (Frontiers in Cellular and Infection Microbiology, 2017)
The DsbA homolog of Francisella tularensis was previously demonstrated to be required for intracellular replication and animal death. Disruption of the dsbA gene leads to a pleiotropic phenotype that could indirectly affect a number of different cellular pathways. To reveal the broad effects of DsbA, we compared fractions enriched in membrane proteins of the wild-type FSC200 strain with the dsbA deletion strain using a SILAC-based quantitative proteomic analysis. This analysis enabled identification of 63 proteins with significantly altered amounts in the dsbA mutant strain compared to the wild-type strain. These proteins comprise a quite heterogeneous group including hypothetical proteins, proteins associated with membrane structures, and potential secreted proteins. Many of them are known to be associated with F. tularensis virulence. Several proteins were selected for further studies focused on their potential role in tularemia's pathogenesis. Of them, only the gene encoding glyceraldehyde-3-phosphate dehydrogenase, an enzyme of glycolytic pathway, was found to be important for full virulence manifestations both in vivo and in vitro. We next created a viable mutant strain with deleted gapA gene and analyzed its phenotype. The gapA mutant is characterized by reduced virulence in mice, defective replication inside macrophages, and its ability to induce a protective immune response against systemic challenge with parental wild-type strain. We also demonstrate the multiple localization sites of this protein: In addition to within the cytosol, it was found on the cell surface, outside the cells, and in the culture medium. Recombinant GapA was successfully obtained, and it was shown that it binds host extracellular serum proteins like plasminogen, fibrinogen, and fibronectin.